Minorities and the Theory of Recognition of Charles Taylor - Raad Abdul Jalil Ali; Najeeba Ibrahim Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
This research seeks to shed light on the Canadian philosopher Charles Taylor's analysis on his theory regarding recognition as well as to the condition of minorities within the policy of cultural pluralism framework, in which he ends in his political and ethical philosophy to a crucial point that is Non-recognition could be considered as kind of cultural oppression, because the exclusion of identity and the exclusion of culture the original considered an urgent requirement because the groups that bear the soreness of recognition are living in a state of constraint for the demand to recognition with the differentiation. Recognition with the distinctions means that the state need pay attention to the calls of individuals and different groups that demand recognition for their cultural and historical peculiarities. Plus, this recognition will not be only because of the recognition and the rejection of the dominance of the culture of the majority only, but an acknowledgment that primarily aims to listen and acceptance the peculiarities of the other, even if it is minority, due to the inevitable impacts on the life of the group and moral and existential of the individual’s life. This is because the recognition of the other cultural, ethnic, and religious distinctions is tolerance in itself, openness, acquaintance with the other, and contentment living with its differences. These benefits are recognition that Tayler may not support it alone, but liberal philosophers like Kimilka. Therefore, recognition is with cultural peculiarities and distinctions not recognized as the soil in which it develops freedoms of individuals and purposes of groups in it and minorities only, but also contribute significantly to motivate social inclusion and political participation. If specific culture is original, it is spared the originality of the individual and it will grow inside it and the spirit of the group and its entity. Thus, neglecting it politically and legally is considered a dangerous punch that harms the benefits of recognition over the unity of society and its cohesion. Therefore, Recognition of the minorities, for example, would encourage the acceptance of differences and involvement in the wider cultural content. Hence, the historical majority culture identified. In which refusal of recognition means is a leap in the unknown because ethnic and cultural groups will reject at the worst appreciation for engaging and integrating into a society that does not value its privacy and does not respect its differentiation. Eventually, this affects the unity, security and safety of society negatively. Therefore, According to Taylor there is no risk, if the majority group recognize the particularities of resident or hosted minorities recently, because the western social or social imagination content is flexible in its structure, host in its values, tolerant in its habits, and this means that western societies refuse historical inertia and imperative considering what they enjoy traditionally in terms of freedom, tolerance and openness. And accepting other cultures considered as a proof of the ability of the original content to adopt other cultures and customs that do not impact it negatively or threaten its existence, but rather this could be a positive progressive factor towards the inclusion of the historical groups, its acculturation and reciprocity.